Is SARS-CoV-2 vertical transmission still a current problem? A case report on a diagnosed SARS-CoV-2 infection with a positive sample of urines. - Bacchini, Pier Luigi; Sammartano, Antonino; Manfredi, Piera; Bidetti, Maria Luisa; Malpeli, Monica; Magliani, Magda; Maradini, Fabio; Ippolito, Luigi (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Current data suggest little to no possibility of original COVID-19 transmission in pregnant women to the fetus during pregnancy or childbirth. Warning with Omicron new variants has decreased.Case report: A clinical case of a SARS-CoV-2 virus transplacental infection of a newborn, born at the end of 2022, from a mother who tested positive for Sars-covid-2 and positive IgM SARS-CoV-2 anti-virus. The newborn tested positive for SARS-CoV-2 12 hours after birth, and was clinically symptomatic after three days, an increase in IgM antibodies was not found, although the virus was identified in the urine samples through molecular tests. The insufficient time to determine the presence of antibodies and the immune system’s state of immaturity can explain the lack of IgM in the newborn’s blood at 14 days after birth.Conclusions: The Omicron SARS-CoV-2 keeps provoking infections among newborns, especially if the mother contracts it during the third trimester. The host response is most likely influenced by the newborn’s peculiar state of immune immaturity. Just before birth, a positive nasal swab and the presence of a positive urine examination confirmed the diagnosis of intraplacental exposure. Research on the virus through molecular tests of urines can represent an additional technique when an aetiological framework of the infection is necessary and a distinction between congenital and post-natal forms.